Popularyzacja wiedzy w mediach lokalnych leszczyńskiego regionu wydawniczego - Jurga-Wosik, Ewa (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2015)
Media lokalne leszczyńskiego regionu wydawniczego (obszar byłego województwa leszczyńskiego) w znacznej mierze, bez względu na rodzaj wydawcy popularyzują wiedzę, zwłaszcza z zakresu nauk humanistycznych. Czasopisma naukowe z kolei nawiązują w szerszym zakresie do wiedzy z zakresu nauk ścisłych, aniżeli pozostałe typy mediów. W czasopismach lokalnych, wydawców samorządowych, jak i prywatnych dominuje wiedza z zakresu badań regionalistycznych. W tego typu prasie nie brakuje również artykułów z dziedziny psychologii, pedagogiki, dietetyki, kosmetologii i nowinek z zakresu rolnictwa. Popularyzacja nauki w mediach lokalnych leszczyńskiego regionu trwa nieprzerwanie od momentu powstania prasy lokalnej na szeroką skalę na badanym obszarze, a zatem od połowy XIX wieku. Celem niniejszej publikacji jest przedstawienie tytułów leszczyńskiego regionu wydawniczego regularnie zamieszczających publikacje naukowe i popularnonaukowe oraz zwrócenie uwagi na potrzebę czytelniczą tego typu treści.

Regardless of the type of publisher, the local press of the Leszczyñski publishing area (covering the territory of the former Leszczyñski region) is to a large extent committed to the promotion of knowledge, particularly in the field of the humanities. Academic periodicals, in turn, mainly promote the knowledge of the exact sciences to a larger extent than other types of media. In local periodicals, whether owned by the local government or private owners, topics related to regional studies dominate. There is also an abundance of articles in the field of psychology, pedagogy, dietetics, cosmetology and innovations in agriculture in this type of periodical. The local media of the Leszczyñski area have been committed to the promotion of knowledge since the beginnings of the local press there, that is since the middle of the 19 th century. The purpose of this paper is to present the periodicals issued in the Leszczyñski publishing area that regularly publish academic and popular articles and to emphasise the readers’ demands for such content.
Promotion of knowledge in the local media of the Leszczyñski publishing region
Keywords: popularyzacja wiedzy; media lokalne; leszczyński region wydawniczy; promotion of knowledge; local media; Leszczyński publishing area